I can [videorecording (DVD)] - Mitchum, Evan; Roebuck, Daniel, 1963-; Wells, Vernon, 1945-; Arnett, Cameron, 1960- (Mill Creek Entertainment, 2023)
Based on a true story, a couple's adulterous affair leads to an unexpected pregnancy. They leave their spouses to begin a new life together, but their daughter, Katelyn, is born with a birth defect. While her dad believes Katelyn's condition is God's punishment for the affair, Katelyn, with only one fully developed arm, defies all odds with an incredible gift for softball. As she overcomes adversity, her father begins to find his way to self-forgiveness.